2004
DOI: 10.1029/2004gl020500
|View full text |Cite
|
Sign up to set email alerts
|

Analytical 2D model to invert hydraulic pumping tests in fractured rocks with fractal behavior

Abstract: [1] A solution to interference pumping tests in fractal fractured media of Euclidean dimension two has been developed. It is proposed in dimensioned variables with a pre-conditioning of its most sensitive parameter and a Gauss-Newton inversion. The method allows for a rapid identification of hydrodynamic parameters by fitting experimental data. The fractal dimension and the scale exponent of the hydraulic diffusion are also determined without any other calculation or reference to a theoretical medium. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Using the diagnostic plot allows for the replacement of all these specialized tools with a simple and unique approach that can be applied to any new solutions, as it has been done for example by Hamm and Bideaux (1996), Delay et al (2004), or Beauheim et al (2004). Today most of the theoretical works related to well testing include diagnostic plots both in hydrogeology and the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…Using the diagnostic plot allows for the replacement of all these specialized tools with a simple and unique approach that can be applied to any new solutions, as it has been done for example by Hamm and Bideaux (1996), Delay et al (2004), or Beauheim et al (2004). Today most of the theoretical works related to well testing include diagnostic plots both in hydrogeology and the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, D cannot be determined without a prior guess on h, and vice versa. Recently, Delay et al (2004) have proposed an approximate solution for cylindrical radial flow (Euclidean dimension d = 2) in a fractal fractured medium, but handling dimensional variables. This solution can be inverted directly on observation data and does not require any additional modeling exercise or prior information to get all the parameters, including D and h.…”
Section: Introductionmentioning
confidence: 99%
“…Then the method by Delay et al (2004) for obtaining the dimensional solution is shown. This solution is compared to the Chang and Yortsos model under various conditions to address its relevance and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the specific research topics explored in the HES is the investigation of spatial variability of hydrodynamic parameters by multiple hydraulic-tests in the geometric well array (Delay et al, 2004). As a part of this study, a large number of slug tests (about 100) were performed in order to estimate the hydraulic conductivity of the aquifer in the vicinity of boreholes.…”
Section: Slug Test Experimentsmentioning
confidence: 99%